GAYA BAHASA DAN FUNGSI DALAM NOVEL 红高粱 (HONG GAOLIANG) KARYA MO YAN - Niza Ayuningtias; Indah Sari (Jurnal Asosiasi Program Studi Mandarin Indonesia (Jurnal APSMI), 2017)
Literature (novel) uses language as a means of communication. Thus, language plays an important role in expressing a writer’s thought. The title of the research was “ The Analysis on Figurative Style in the Novel, 红高粱 (hóng gāoliang), by Mo Yan. ” In this research, the writer analyzed Mandarin  figurative style found in the novel, 红高粱 (hóng gāoliang). The research used the concept of Mandarin figurative style by Huang and Liao and descriptive qualitative method. The data of Figurative Style was obtained from the novel, 红高粱 (hóng gāoliang) by Mo Yan , published in 2012. The result of the research showed that there were nine types of figurative style in the novel, 红高粱 (hóng gāoliang) by Mo Yan: figurative style of比喻(bǐyù),比拟(bǐnǐ),夸张(kuāzhāng),借代(jièdài), 反语(fǎnyǔ),层递(céng dì),反复(fǎnfù), 映衬(yìngchèn), and 对偶(duì'ǒu). The role of figurative styles was as follows: 1)比喻(bǐyù) figurative style gave the effect of beauty in the story, made the content of the story more interesting and concrete, and gave profound impression to the readers, 2) 比拟(bǐnǐ) figurative style made the story more interesting, more animated, and not monotonous , 3) 夸张(kuāzhāng) figurative style changed the simple language to an interesting one, 4) 借代(jièdài) figurative style made the language and the words varied, 5) 反语(fǎnyǔ) figurative style expressed satire and the sentence looked humorous, 6) 层递(céng dì) figurative style gave the impression of greatness, 7) 映衬(yìngchèn) figurative style made the atmosphere in the story more expressive, 8) 反复(fǎnfù) figurative style emphasized on a problem and expressed a certain feeling, and 9) 对偶(duì'ǒu) figurative style gave explicit intention to its readers.Keyword: Literature, Novel, Figurative Style